The mechanism of synergistic hydration performance improvement of the ternary composite cementitious material composed of hemihydrate phosphogypsum, blast furnace slag and quicklime - Li, Jianqiu; Li, Yulu; Yang, Lin; Cao, Jianxin (Frontiers in Materials, 2026)
To realize the resource utilization of solid waste hemihydrate phosphogypsum (HPG) and significantly enhance its mechanical strength and water resistance as a construction material, this study employs the synergistic activation of HPG with blast furnace slag (BFS) and quicklime. A high-strength and highly water-resistant HPG-based ternary composite cementitious material (HPG-CCM) was prepared. Systematic investigations on its leaching toxicity, hydration characteristics, and microstructural evolution were conducted through ICP-OES, XRD, SEM-EDS, and TG-DTG analyses. The results demonstrate that when the HPG-to-BFS mass ratio was 6:4 with 3% externally added quicklime, the 28-day compressive strength and softening coefficient of HPG-CCM reached 52.8 MPa and 0.97, respectively. Under this optimal formulation, the relative proportions of C-S-H gel and ettringite in the reaction system were effectively modulated, resulting in significantly enhanced structural compactness, suppressed volumetric expansion, and improved water resistance. Furthermore, when the external quicklime content exceeded 3%, the leaching concentrations of phosphorus (P) and fluorine (F) remained below the thresholds stipulated by the Chinese standard GB 8978-1996, confirming the material’s exceptional safety. Mechanistic analysis reveals that the hydration process of HPG-CCM comprises three distinct phases: Early Hydration Stage: Quicklime neutralized the inhibitory effects of soluble P and F within HPG on its hydration activity, facilitating the formation of interlocking CaSO4·2H2O crystals that established the primary strength framework. Densification Stage: Active silicates and alumina from BFS reacted with quicklime and CaSO4·2H2O to generate C-S-H gel and ettringite, which filled interstitial pores within the CaSO4·2H2O matrix, yielding a dense microstructure. Encapsulation Stage: Continuous hydration of BFS produced C-S-H gel that progressively enveloped CaSO4·2H2O crystals, thereby augmenting both mechanical robustness and water resistance.